Participation Of Riverbank Communities In Development (Case Study Of Riverbank Communities In Kelayan Timur Urban Village, South Banjarmasin Sub-District, Banjarmasin City) - Suriyani, Erna (International Journal of Educational Research & Social Sciences, 2025)
This research aims to find out how riverbank community participation in development in Kelayan Timur Village. The type of research used in this research is descriptive, while the approach used is a qualitative approach. Data collection was done through observation, interviews, and documentation. The research findings show that the riverbank community in Kelayan Timur Village in overall development is quite participatory, but not maximized. Community participation in decision-making is quite good, such as the delivery of aspirations, ideas, input, suggestions and criticism from the community, although it has not been done directly by the community. Community participation in the implementation of development activities already exists but is still low, both in terms of providing labor and materials. Community participation in monitoring and evaluating development activities is quite good. Meanwhile, community participation in the utilization of development results is good but the maintenance of development results is still low.